Interconnected risks: Exploring the nexus of zoonosis and climate change - Sara Basiri (Journal of Zoonotic Diseases)
Climate change is the twenty-first century's most significant threat to human health. Human activity has led to a gradual increase in greenhouse gas concentrations, resulting in global warming and other related hazards. Climate change is significantly impacting ecosystems and biodiversity, leading to a potential increase in zoonotic diseases. Zoonoses are infectious diseases that are transmitted among animals and humans. Vector-borne, foodborne, and waterborne diseases are major infectious diseases associated with climate change. Changes in temperature and precipitation patterns influence the survival, reproduction, and activity of disease-carrying vectors like mosquitoes, ticks, and sandflies. Variations in climate can affect the spread of diseases such as malaria, leishmaniasis, and rodent-borne illnesses like leptospirosis, bartonellosis, plague, and hantavirus infections. Climate change can also impact waterborne illnesses by altering water quality and increasing the risk of contamination during natural disasters. Additionally, higher temperatures and increased humidity can cause transmission of airborne zoonotic diseases, such as aspergillosis, tuberculosis, and influenza. The evolving climate may also contribute to the development of resistance in disease-causing microorganisms, making treatment more challenging. Human behavior influenced by climate change, such as changes in agricultural practices and land use, can indirectly affect disease transmission by altering vector habitats and human-animal interactions. Overall, the complex interplay between climate change, ecological factors, and human behavior underscores the need for comprehensive strategies to mitigate the risks posed by zoonotic diseases and protect public health.